2022
DOI: 10.3390/ijms23147873
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Base Synchondrosis Lacks PTHrP-Expressing Column-Forming Chondrocytes

Abstract: The cranial base contains a special type of growth plate termed the synchondrosis, which functions as the growth center of the skull. The synchondrosis is composed of bidirectional opposite-facing layers of resting, proliferating, and hypertrophic chondrocytes, and lacks the secondary ossification center. In long bones, the resting zone of the epiphyseal growth plate houses a population of parathyroid hormone-related protein (PTHrP)-expressing chondrocytes that contribute to the formation of columnar chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, the exact relationship between the SOC and this growth plate stem cell population remains to be elucidated. In our recent study, we examined the presence of a Pthrp -expressing stem cell population in synchondroses [ 42 ]. Surprisingly, Pthrp expressing cells were found predominantly within a wedge-shaped structure on the lateral borders of the SOS.…”
Section: Molecular Regulation Of the Cranial Basementioning
confidence: 99%
“…However, the exact relationship between the SOC and this growth plate stem cell population remains to be elucidated. In our recent study, we examined the presence of a Pthrp -expressing stem cell population in synchondroses [ 42 ]. Surprisingly, Pthrp expressing cells were found predominantly within a wedge-shaped structure on the lateral borders of the SOS.…”
Section: Molecular Regulation Of the Cranial Basementioning
confidence: 99%
“…Different with majority skull bones are formed via intermembranous ossification, in which mesenchymal cells differentiate into osteoblasts to form bones (Nakashima & de Crombrugghe, 2003), bones in the cranial base are developed by endochondral ossification, which cartilage are replaced into bones, similar with bones in the trunk and extremities (Rengasamy Venugopalan & Van Otterloo, 2021; Young et al, 2006). Unlike endochondral ossification in the long bones, synchondroseal growth is bidirectional (Bailleul & Horner, 2016; Hallett et al, 2022). We recently reported that a feedback loop between Indian hedgehog and parathyroid hormone‐related protein (PTHrP) plays critical roles in the posterior‐to‐anterior ossification of cartilage primordia in the cranial base (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that a feedback loop between Indian hedgehog and parathyroid hormone‐related protein (PTHrP) plays critical roles in the posterior‐to‐anterior ossification of cartilage primordia in the cranial base (Zhang et al, 2022). Interestingly, however, PTHrP‐expressing cells, which contribute to formation of columnar chondrocytes in long bones, do not contribute to the formation of columnar structures in synchondrosis (Hallett, Zhou, et al, 2022). These facts suggest that there are different molecular cellular mechanisms of endochondral ossification between the cranial base and the long bones.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any abnormalities of the synchondroses could affect skull and midfacial morphologies (Wei et al 2016; Funato 2020). A recent review identified Runt-related transcription factor 2 (RUNX2), the T-box transcription factor family 1 (TBX1), the fibroblast growth factor receptor family (FGFRs), the parathyroid hormone–related protein (PTHrP) pathway, the Indian hedgehog (IHH) pathway, the cilium assembly, and the Wnt/β-catenin pathway as some of the factors regulating synchondrosis development (Wei et al 2016; Funato 2020; Hallett, Ono, et al 2022; Hallett, Zhou, et al 2022).…”
Section: Introductionmentioning
confidence: 99%